Bahasa, Stigma, dan Perubahan Sosial: Merekonstruksi Identitas Lokal melalui Program Pelestarian Bahasa Wemale - Iyon, Gilbert Risky; Salakay, Selvianus (Universitas Pattimura, 2023)
This article analyzes the roles of families, schools, and village governments in preserving the Wemale language in West Seram Regency, Maluku, with a focus on the unequal contributions among actors and the social stigma attached to the use of local languages. It also examines how community-based programs such as the Community Learning Center (PKBM) serve as spaces for reconstructing local identity through the use of Wemale in informal and nonformal educational settings. Employing a qualitative case study approach, data were collected through in-depth interviews, participant observation, and document analysis in villages with active Wemale-speaking communities. Thematic analysis was used to identify patterns in language use, social perceptions, and preservation strategies by local actors. The findings reveal that families’ role in language transmission has weakened due to modernization, digital influences, and stigma associating the Wemale language with backwardness. In contrast, schools and PKBM demonstrate more active engagement, particularly through alternative learning spaces such as Walang Belajar, which utilize contextual approaches to connect youth with the local language. However, actor coordination remains weak and affirmative policies supporting Wemale as a source of collective identity are absent. This study offers a novel intersection of language, social stigma, and identity politics in Eastern Indonesia while highlighting PKBM’s strategic role in minority language preservation.